A follow‐up report on the effect of a simplified basic life support training program for non‐medical staff working at a university hospital: changes in attitude toward cardiopulmonary resuscitation and automated external defibrillator use through repeat training. Issue 1 (6th August 2020) - Matsuura, Hiroshi; Sakai, Tomohiko; Katayama, Yusuke; Kitamura, Tetsuhisa; Hirose, Tomoya; Matsumoto, Hisatake; Matsubara, Tsunehiro; Iwami, Taku; Fujino, Yuji; Shimazu, Takeshi
Abstract : Aim: This study aimed to investigate the effect of repeat training and the interval of reattending a simplified basic life support (BLS) training course. Methods: We administered a questionnaire on the attitude toward cardiopulmonary resuscitation (CPR) and automated external defibrillator (AED) use (check for response, chest compression, and using an AED) before and immediately after a 45‐min BLS training program provided for non‐medical staff working at a university hospital from September 2010 to November 2018. The main outcome was positive willingness of the participants toward CPR and AED use. The effect of repeat training was assessed with McNemar's test and multivariable logistic regression analysis. Differences in the interval of reattending the simplified BLS training course were assessed with Fisher's exact test. Results: Fifty‐nine training courses were held. Among the total participant count of 1, 025, 760 individuals attended, of whom 126 attended the training multiple times. The proportion of participants showing a positive attitude toward chest compression before the course increased as the number of attendances increased (adjusted odds ratio 1.62: 9.8% at first training to 58.8% at sixth training). The positive attitude of participants before the course was significantly greater when the training interval was <1 year (36.1% versus 18.7%). There was no significant difference for a 6‐month interval (40% versus 23.2%). Conclusions: Repeat training for non‐medical staff in a chest compression‐only CPR training course showed a cumulative effect of repeat attendance. A course interval of <1 year from the previous attendance would be important for maintaining a positive attitude toward CPR and AED use. Abstract : We showed the cumulative effect on the attitude of non‐medical workers to basic life support (BLS) skills by taking the simplified BLS training multiple times. From the results of this study, we clarified that repeating an annual cardiopulmonary resuscitation (CPR) training course for non‐medical workers improves their attitude toward performing CPR.